Metode Inkuiri dalam Pembelajaran Menyimak Arab di PKPBA UIN Maulana Malik Ibrahim Malang pada Masa Pandemi Covid-19 - Zamroni, M.; Supriyanto, Supriyanto (UIN Maulana Malik Ibrahim Malang, 2021)
This study aims to explain the process of Arabic listening learning using the inquiry method to PKPBA students at UIN Maulana Malik Ibrahim Malang during the Covid-19 pandemic. The research design implemented in this study is a mixed-method, with a sequential exploratory strategy research design. In which researchers collect, analyze, reduce, and draw conclusions from research data by mixing qualitative and quantitative methods. While the data collection technique is done by the triangulation technique which includes observation, documentation, and literacy. The research subjects in this study were students of ST.1 class of the Faculty of Science and Technology. The results of this study indicate that there are three stages in learning Arabic listening with this method, namely the preliminary, the core learning, and the closing. And six main stages can be implemented with the inquiry method for learning to listen to Arabic, namely the orientation, formulating problems, making hypotheses, collecting data, testing hypotheses, and formulating conclusions. Furthermore, the inquiry method was effective in increasing student activity, as evidenced by the increase in their scores from the mean value of 13.69 to 18.24. In addition, the inquiry method was also effective in increasing the value of understanding the meaning of instructional videos, as evidenced by their scores before using the inquiry method had a mean of 73.98 increasing to 81.98. This method is also effective in increasing the fluency in demonstrating simple expressions, as evidenced by their scores before using the inquiry method with a mean of 72.92 increasing to 82.58.